2018
DOI: 10.1002/jwmg.21450
|View full text |Cite
|
Sign up to set email alerts
|

Black‐backed woodpecker abundance in the Black Hills

Abstract: The Black Hills population of black‐backed woodpeckers (Picoides arcticus) was petitioned, but deemed not warranted, to be listed as a threatened or endangered species under the Endangered Species Act and more information on their population size in the region is needed. Our objective was to map abundance and provide a population estimate of black‐backed woodpeckers in the Black Hills and Bear Lodge Mountains of South Dakota and Wyoming, USA. We conducted 3,666 and 3,384 5‐minute point count surveys from late‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In addition, both studies found evidence of nesting in green forest, although they reported nesting densities that were lower than what is typically found within recently burned areas (Fogg et al 2014, Verschuyl et al 2021). Taken together, these findings expand upon previous investigations that have found the Black-backed Woodpecker nesting in green forest in other parts of its range, including the boreal forest of eastern Canada (Tremblay et al 2009, 2015b) and in ponderosa pine ( Pinus ponderosa ) forest of the Black Hills, South Dakota, USA, following mountain pine beetle ( Dendroctonus ponderosae ) outbreaks (Bonnot et al 2008, Rota et al 2014, Matseur et al 2018). These studies further suggest that green forests may support productive nesting Black-backed Woodpecker populations in the western part of its range, which is contrary to the notion that green forests act as population sinks for this species (Hutto 1995).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, both studies found evidence of nesting in green forest, although they reported nesting densities that were lower than what is typically found within recently burned areas (Fogg et al 2014, Verschuyl et al 2021). Taken together, these findings expand upon previous investigations that have found the Black-backed Woodpecker nesting in green forest in other parts of its range, including the boreal forest of eastern Canada (Tremblay et al 2009, 2015b) and in ponderosa pine ( Pinus ponderosa ) forest of the Black Hills, South Dakota, USA, following mountain pine beetle ( Dendroctonus ponderosae ) outbreaks (Bonnot et al 2008, Rota et al 2014, Matseur et al 2018). These studies further suggest that green forests may support productive nesting Black-backed Woodpecker populations in the western part of its range, which is contrary to the notion that green forests act as population sinks for this species (Hutto 1995).…”
Section: Introductionsupporting
confidence: 85%
“…To cover the range of green forest used by Black-backed Woodpeckers in the broader landscape, we targeted our searches to green forest that was classified as 1 of the 4 composition types described above (i.e., lodgepole pine, ponderosa pine, mixed conifer, and mixed pine) and contained potential nest trees of a minimum of 15-cm DBH (Verschuyl et al 2021). The green forest areas we nest-searched were generally absent of major disturbance, differentiating our study from prior research in green forest dominated by beetle-killed trees (Bonnot et al 2008, Rota et al 2014, Matseur et al 2018, Tingley et al 2020. We also searched for nests in recently burned conifer forest in areas that were interspersed with green forest throughout our focal landscape (Figure 1), including the 2017 North Pelican Fire (1,452 ha), the 2017 Blanket Creek Fire (13,484 ha), the 2018 Timber Crater 6 Fire (1,265 ha), the 2020 Thielsen Fire (4,037 ha), and the 2020 Two Four Two Fire (5,857 ha).…”
Section: Nest Searching and Monitoringmentioning
confidence: 99%
“…Animals with stable territories, specialized diets and narrow habitat choices, such as some woodpecker species, are known to adjust their space use and movements based on the spatio-temporal heterogeneity of habitat resources [1,2]. Those animal species concentrate their movements in the habitats of higher foraging quality [3,4], [5,6,7], a behavior known as area-restricted search (ARS) that, in many cases, involves the use of spatial memory to return to suitable sites within territories [8,9]. Determining the areas where animals concentrate their movements and foraging activity not only contributes to understand decision-making behavior or foraging e ciency but also to the identi cation of feeding areas important for the conservation of vulnerable species [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is a worldwide interest in identifying tools for effective estimation of species population size and removal models show great potential for application in a wide range of situations, such as species relocation projects and control of exotic invasive species. Even if the original aim of this method was to deplete a species, and some of the studies included in this review use the method for this purpose [ 2 , 22 , 107 , 108 , 113 , 117 , 119 ], most of the studies included in this review were focused on understanding abundance of a particular species due to general interest (for example [ 78 , 81 84 , 88 , 143 ]). However, as a management tool it has been used not only to estimate abundance [ 12 , 144 ], but also, to estimate catchability [ 35 , 66 , 68 , 109 , 118 ], migration [ 13 , 43 , 71 , 85 ], habitat selection [ 64 , 77 , 96 ], endangered species [ 26 , 116 , 145 ], population dynamics [ 90 , 103 , 124 ] or translocation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%